Penerapan Dinar dan Stabilitas Ekonomi: Pendekatan Vector Autoregression - Rusydiana, Aam Slamet (Universitas Islam Negeri Raden Intan Lampung, 2017)
The application of fiat money in transaction makes unstability in economy. To solve this problem, it needs a strong monetary system that support by stabil currency. This research is going to analyze the impact of dinar on economic stability in Indonesia. This study use vector error correction model as tool of analysis. The result shows that exchange rate had negative impat of economic growth, but dinar give a positive impact on economic growth. Besides that, the dinar doesn’t give an impact on inflation increasing in Indonesia. This result imply that the application of dinar will make an economy relatively stabil than fiat money currency.